2019
DOI: 10.1021/acs.joc.9b01634
|View full text |Cite
|
Sign up to set email alerts
|

Isoxazole Strategy for the Synthesis of α-Aminopyrrole Derivatives

Abstract: The synthesis of methyl 5-aminopyrrole-3-carboxylates from 4-methyleneisoxazol-5-ones via "cyanide Michael addition/methylation/reductive isoxazole-pyrrole transformation" is developed. The last step occurs in a domino mode involving Mo(CO) 6 -mediated reductive isoxazole ring-opening, Mo(CO) 6catalyzed cis−trans-isomerization of the enamine intermediate followed by 1,5-exo-dig cyclization. 5-Amino-1H-pyrrolo-3-carboxylates react with 1,3-diketones, affording pyrrolo[1,2-a]pyrimidine-7-carboxylates, and are ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…This protocol (Scheme 2) was further exploited to study its versatility, by subjecting various substituted aromatic aldehydes as well as heteroaromatic aldehyde to give corresponding Isoxazolones in very good yields (Table 2). Characterization studies of prepared compounds revealed parallel similarities with the reported literature data and undoubtedly supported the assigned structures [25–44] …”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This protocol (Scheme 2) was further exploited to study its versatility, by subjecting various substituted aromatic aldehydes as well as heteroaromatic aldehyde to give corresponding Isoxazolones in very good yields (Table 2). Characterization studies of prepared compounds revealed parallel similarities with the reported literature data and undoubtedly supported the assigned structures [25–44] …”
Section: Resultssupporting
confidence: 81%
“…Literature analysis [20–44,55–57] revealed this synthetic methodology to be one of the robust method for preparing Isoxazolone derivatives with more labile functional groups. Thus provide scope for development of functionally sensitive or even optically active Isoxazolones, keeping in mind their growing importance in medicinal field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature survey on pyrrole synthesis between 2014 and 2019 also revealed interesting strategies in which different classes of heterocycles have been effectively employed as starting materials. [126][127][128][129][130][131][132][133][134][135] Some examples discussed in this section include münchnones, isoxazoles, carbohydrates, hydroxyprolines, and pyrrolines. It is interesting to note that these heterocyclic motifs readily produce pyrroles that are densely substituted.…”
Section: Review Synthesis 5 From Heterocyclesmentioning
confidence: 99%
“…This is actually a limitation, not only for pharmaceutical applications, but it has also practical issues for product characterization, HPLC analysis and determination of diastereo‐ and enantiomeric ratios. As a consequence, Michael adducts of alkylideneisoxazol‐5‐ones have attracted a limited attention and they have mainly served as non‐isolated intermediates in further transformations , , , , …”
Section: Introductionmentioning
confidence: 99%